Planejamento estratégico da tecnologia da informação em uma universidade pública - Schebeleski, Marcos (2009)
Currently the Information Technology (IT) is of vital position in the corporate environment, because that provides the infrastructure on which to set out the specific information systems and technology services. The process of IT management is extremely complex and susceptible to themselves and various aspects. Public university that diversity still absorbs aspect of the sector, activities, culture and installed and especially to legacy technology. The Strategic Planning of Information Technology - SPIT established itself as a tool increasingly essential to optimize the use of information technology in organizations. Thus, this work is developed in order to examine the organizational and administrative setting of a Public University, and before its Institutional Development Plan - IDP, outlining a methodology for the establishment of a SPIT the State University of Maringá - UEM. This research is characterized as descriptive and qualitative, is founded on analysis of important methodologies SPIT present in the literature, the search for significant elements contained in the IDP, by the documental analysis, leading to an understanding of the process of strategy Institution, and the analysis of organizational characteristics identified through interviews, with respect to its installed base, legacy systems and perspectives according to their demands, aspirations and trends of IT. Among the results, it has been the design of a methodology for SPIT consists of five phases of implementation relating to: diagnosis of the state, the establishment of strategies, preparation for the implementation of the plan, plan implementation, and monitoring and control, being that the composition of these phases took into account the particular characteristics and strategies of the institution.